Pilot Project Panduan Bagi Guru dan Fasilitator untuk Pengembangan Keterampilan Sosial Anak di Desa Pasirtanjung - Erik; Maulana, Herdiyan; Gumelar FR, Gumgum; Yudhita, Liza (Universitas Negeri Jakarta, 2024)
Social skills are essential for everyone to have. The cultivation and development of social skills are essential for children. From an early age, children need to be instilled and developed with social skills to face life in school and society well. The cultivation and development of social skills for children are crucial, considering the changing times that can make children lack social skills. For example, the rapid development of information technology, mobile phones, online games, and other communication media can make a person’s skills, especially children’s, less developed or even decline. Therefore, it is very important to develop social skills for children. Besides parents, teachers and facilitators at school also play a crucial role in developing children’s social skills. However, with this module-shaped instrument, guidance for teachers and facilitators to develop children’s social skills becomes crucial. In this community service, a pilot project will be carried out to guide teachers and facilitators to develop children’s social skills. Teachers and facilitators will dissect and provide input on the guide so that it can be used later according to its purpose to develop children’s social skills.